1992
DOI: 10.1007/bf00271037
|View full text |Cite
|
Sign up to set email alerts
|

Identification of brush cells in the alimentary and respiratory system by antibodies to villin and fimbrin

Abstract: Brush cells represent a population of epithelial cells with unknown function, which are scattered throughout the epithelial lining of both the respiratory system and the alimentary system. These cells are reliably distinguished from other epithelial cells only at the ultrastructural level by the presence of an apical tuft of stiff microvilli and extremely long microvillar rootlets that may project down to the perinuclear space. In the present study we show that brush cells can be identified in tissue sections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 32 publications
2
73
0
3
Order By: Relevance
“…§1734 solely to indicate this fact. against a-gustducin and the actin filament-bundling protein villin, a marker molecule for brush cells (10,12), identified these cells as brush cells (Fig. 1 D and E).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…§1734 solely to indicate this fact. against a-gustducin and the actin filament-bundling protein villin, a marker molecule for brush cells (10,12), identified these cells as brush cells (Fig. 1 D and E).…”
Section: Resultsmentioning
confidence: 93%
“…Binding of taste molecules to these receptors is thought to induce GTP binding to a-gustducin that, like other G,-proteins, stimulates second messenger systems involved in signal transduction. The lumenal cell pole of both brush cells (4,5,6,12) and taste receptor cells (11) contains numerous microvilli that are the most likely site for chemoreception. In support of this notion, we found that the lumenal cell pole of both cell types was the most strongly immunolabeled portion.…”
Section: Discussionmentioning
confidence: 99%
“…Such cell populations express T2Rs, gustducin, PLCβ2, and TrpM5 as well as other markers of taste cells. Despite this similarity in molecular expression, these diverse cells in different organ systems are not identical despite their sometimes being lumped together under the term "brush cells" (35). For example, the gustducin-positive cells that we have studied in the nasal cavity are heavily innervated by polymodal nociceptors (1) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Likely owing due to their anatomic restriction to the portal of entry into the urogenital tract (i.e., the urethra and glandular ducts opening into it), these chemosensory cells have escaped detection in previous searches for urogenital brush cells that focused on more centrally located organs, including the kidney, uterus, and prostate gland, before the sentinel function of solitary chemosensory cells had been proposed (14). Coexpression patterns of various components of the taste transduction cascade and ChAT-eGFP suggest the presence of more than one chemosensory cell type in the urethra, including a cholinergic type using PLCβ2 and TRPM5, proteins essential for oropharyngeal bitter and umami perception (27), for downstream signaling.…”
Section: Discussionmentioning
confidence: 99%
“…2D and Table S2) and at the ultrastructural level exhibit a tuft of apical microvilli and additional basolateral microvilli (Fig. 2 F and G), the defining features of respiratory and gastrointestinal brush cells (14). A significant additional population of urethral villin-positive cells (≥50%) lacked ChAT-eGFP fluorescence (Fig.…”
Section: Significancementioning
confidence: 91%